A duration-dependent response to isolated leg cooling exists for intermittent-sprint exercise in the heat - Smith, D.; Ross, E.; Watt, P.; Maxwell, N. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Leg precooling has been used as an effective ergogenic aid to reduce the negative effects of heat stress that are exacerbated during intermittent sprint exercise. An assumption exists that longer cooling durations may elicit greater benefits through creation of a larger heat sink. The aim of this study was to determine the optimal duration of a single bout of precooling on intermittent sprint performance in the heat. Methods: Twelve males, free from any heat or cold exposure (age 22+/-2 yrs, height 178.1+/-3.9 cm, body weight 76.7+/-7.5 kg, sum of four skinfolds 40.4+/-3.9 mm, peak oxygen consumption 44.9+/-6.1 mL/kg/min) completed five cycling intermittent sprint protocols (CISP) in a randomised order on separate days. The CISP comprised of 20 sets of 10s passive rest, 5s max sprint against 7.5% body weight and 105s active recovery against 35% peak oxygen uptake. Each CISP was preceded by a cooling period of 10, 15, 20, 25 min and a no-cooling control. Peak power output (PPO) and work done (WD) were measured throughout each CISP, alongside the measurement of skin (Tsk) and core (Tc) temperature. Muscle temperature (Tmu) was measured pre cooling and post exercise. Results: Average PPO and WD improved in the 15 and 20 min conditions only (P<0.05). 15 min saw the largest improvements (3.8% and 6.7%, respectively) compared to the Control (P<0.05) but was lowest after 25 min of cooling. Tc during precooling remained unchanged in all trials, but 15 min displayed the slowest rate of Tc rise during the CISP compared to the Control (Control, 0.07+/-0.01 degrees/sprint; 15min, 0.05+/-0.0 degrees/sprint, P<0.05). Mean Tsk was unchanged during all precooling trials yet thigh Tsk was lower than the Control in all conditions (P<0.05). 15 and 20 min cooling reduced thigh Tsk more than 10 min (P<0.05) yet further cooling provided no additional reduction (Control, 30.7+/-1.3; 10min, 13.6 +/- 6.3; 15min, 9.4+/-3.3; 20min, 9.2+/-3.2; 25min, 11.4+/-3.9 degrees C). Tmu reduced the most for longer durations. Post CISP Tmu was only lower than the Control after 15 min cooling with additional periods of time not reducing Tmu further (Control, 38.5+/-1.2; 10min, 37.9+/-1.4; 15min, 37.5+/-1.8, 20min, 37.6+/-1.8; 25min, 38.2+/-1.4 degrees C, P<0.05). Discussion: Findings from this study suggest that 15 min was the optimal duration of localised cooling for improvements in PPO and WD during intermittent sprint exercise in the heat. Cooling for shorter durations may not offer sufficient suppression of thermo-physiological responses before exercise in the heat, while longer durations of cooling may result in too great a thermo-physiological offset to optimise intermittent sprint performance.